Cervicogenic Headache - John Edmeads (Pain Research and Management)
That disease or dysfunction of the neck may present as headache is an idea that is not widely accepted in North American traditional medicine. This review focuses on 'cervicogenic headaches'. Topics include the mechanisms of cervicogenic headache, cervical signs to suspect that a patient's headache originates in the neck, diagnostic manoeuvres that are nonspecific and unreliable, laboratory tests that may assist in establishing a diagnosis of cervicogenic headache and treatment of this condition.